The outlines of the future: digitalisation of the economy and other spheres of human activity - Babosov, Evgenii M. (Journal of the Belarusian State University. Sociology, 2019)
The article presents a number of approaches to the definition of the concept of «digital economy». The essence and basic processes of information and communication revolution are characterized. High labor productivity and inextricably linked with it increase of competitiveness of enterprises are analyzed as the main results of digitalization of the economy. The key features of the rapid digitalization of the economy and other spheres of modern society: the increasing role of subject creative thinking, a significant increase in productivity, the transition to industry 4.0, widespread blockchain, development of the scope of cryptocurrency, intensification of the use of big data are considered.